2007
DOI: 10.1007/s00018-007-7339-9
|View full text |Cite
|
Sign up to set email alerts
|

DNA fragmentation in leukocytes following repeated low dose sarin exposure in guinea pigs

Abstract: The objective of this study was to determine levels of DNA fragmentation in blood leukocytes and parietal cortex from guinea pigs following repeated lowlevel exposure to the chemical warfare nerve agent (CWNA) sarin. Guinea pigs were injected (s.c.) once a day for 10 days with saline, or 0.1, 0.2, or 0.4 LD 50 (50 % mean lethal dose) sarin dissolved in sterile physiological saline. Blood and parietal cortex was collected after injection at 0, 3, and 17 days recovery and evaluated for DNA fragmentation using si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…However, sarin was administered repeatedly for 10 days in above mentioned study. No significant increase in DNA fragmentation in any experimental group at 17 days after sarin exposure was found (Dave et al, 2007). Our results presented in this paper confirm the ability of sarin, soman and tabun to induce the DNA damage in vivo.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…However, sarin was administered repeatedly for 10 days in above mentioned study. No significant increase in DNA fragmentation in any experimental group at 17 days after sarin exposure was found (Dave et al, 2007). Our results presented in this paper confirm the ability of sarin, soman and tabun to induce the DNA damage in vivo.…”
Section: Discussionsupporting
confidence: 83%
“…In the case of poisoning with sublethal doses of nerve agents studied, no significant DNA damage was observed. According to our knowledge, there is only one paper decribing the induction of the DNA damage by sarin in the blood leucocytes and parietal cortex in vivo in guinea pigs, which describes an increase in DNA fragmentation at 0.2 and 0.4 LD 50 , but not at 0.1 LD 50 (Dave et al, 2007). However, sarin was administered repeatedly for 10 days in above mentioned study.…”
Section: Discussionmentioning
confidence: 91%
“…In a case-control study of 594 skin lesion cases and 1041 controls, the dose-response relationship of skin lesion risk was significantly higher in individuals with the 677TT/1298AA and 677CT/1298AA diplotypes in the methylenetetrahydro-folate reductase (MTHFR) enzyme (1.66 and 1.77 respectively), than for those with the 677CC/1298CC diplotype. 165 The OR for skin lesions in relation to the GSTO1 diplotype (Glutathione S-transferase 1) containing all at-risk alleles was 3.91. 166 These early changes in the skin associated with arsenic also predispose to the development of a variety of skin cancers, and a squamous cell carcinoma (in situ) known as Bowen's Disease may also develop.…”
Section: Skin Conditionsmentioning
confidence: 99%
“…The HEALS group of researchers also found that males and elderly people are more affected by arsenic exposure, (Ahsan 2006b) as were those with excessive sun exposure, 161 lower nutritional status, 162,163 and lower socioeconomic status (non-land owners). 164,165 Genetic variability in genes that code for enzymes in arsenic metabolism may also affect individual susceptibility to skin lesions. In a case-control study of 594 skin lesion cases and 1041 controls, the dose-response relationship of skin lesion risk was significantly higher in individuals with the 677TT/1298AA and 677CT/1298AA diplotypes in the methylenetetrahydro-folate reductase (MTHFR) enzyme (1.66 and 1.77 respectively), than for those with the 677CC/1298CC diplotype.…”
Section: Skin Conditionsmentioning
confidence: 99%